Experiences of living without a sense of smell: Like "Being Behind Glass". - Lorenzo D Stafford; Karl Nunkoosing; Mark Haydon-Laurelut; Michael Fisher (PLoS ONE, 2023)
This study addresses the paucity of research concerning the subjective experiences of those affected by anosmia. In the study, we interviewed individuals(n = 11) recruited via the charity (Fifth Sense) and used Interpretative Phenomenological Analysis (IPA) to analyse the data. Findings revealed three main themes and seven sub themes. The main themes are Living with Anosmia; Remembrance of things old and new and Resilience. The study reveals the process of becoming aware of being anosmic and the relationships with others in this process including potentially unhelpful minimisations of the impact by professionals. In addition to a sense of isolation and insecurity, living with anosmia for some participants brought with it an identification of being 'anosmic' and feeling part of a community. This was in contrast to a general lack of public knowledge and understanding of anosmia. The findings of the study demonstrated the importance of smell to time, place and relationship and the recalling of smells as bringing a sense of connectivity to loved ones, of times past and also a sense of loss of ability. Participants also described the ways in which they coped and adapted to a life with anosmia and focused on positive aspects of life. These findings provide a rich qualitative account of the experience of anosmia. The findings point towards future research which could inform us about the lives of those who are anosmic and currently unaware and of those recently diagnosed, which will create a richer understanding of the experiences of anosmia.